Polydatin prevents fructose-induced liver inflammation and lipid deposition through increasing miR-200a to regulate Keap1/Nrf2 pathway - Zhao, Xiao-Juan; Yu, Han-Wen; Yang, Yan-Zi; Wu, Wen-Yuan; Chen, Tian-Yu; Jia, Ke-Ke; Kang, Lin-Lin; Jiao, Rui-Qing; Kong, Ling-Dong (Redox biology, 2018)
Oxidative stress is a critical factor in nonalcoholic fatty liver disease pathogenesis. MicroRNA-200a (miR-200a) is reported to target Kelch-like ECH-associated protein 1 (Keap1), which regulates nuclear factor erythroid 2-related factor 2 (Nrf2) anti-oxidant pathway. Polydatin (3,4′,5-trihydroxy-stilbene-3-β-D-glucoside), a polyphenol found in the rhizome of Polygonum cuspidatum, have anti-oxidative, anti-inflammatory and anti-hyperlipidemic effects. However, whether miR-200a controls Keap1/Nrf2 pathway in fructose-induced liver inflammation and lipid deposition and the blockade of polydatin are still not clear. Here, we detected miR-200a down-regulation, Keap1 up-regulation, Nrf2 antioxidant pathway inactivation, ROS-driven thioredoxin-interacting protein (TXNIP) over-expression, NOD-like receptor (NLR) family, pyrin domain containing 3 (NLRP3) inflammasome activation and dysregulation of peroxisome proliferator activated receptor-α (PPAR-α), carnitine palmitoyl transferase-1 (CPT-1), sterol regulatory element binging protein 1 (SREBP-1) and stearoyl-CoA desaturase-1 (SCD-1) in rat livers, BRL-3A and HepG2 cells under high fructose induction. Furthermore, the data from the treatment or transfection of miR-200a minic, Keap1 and TXNIP siRNA, Nrf2 activator and ROS inhibitor demonstrated that fructose-induced miR-200a low-expression increased Keap1 to block Nrf2 antioxidant pathway, and then enhanced ROS-driven TXNIP to activate NLRP3 inflammasome and disturb lipid metabolism-related proteins, causing inflammation and lipid deposition in BRL-3A cells. We also found that polydatin up-regulated miR-200a to inhibit Keap1 and activate Nrf2 antioxidant pathway, resulting in attenuation of these disturbances in these animal and cell models. These findings provide a novel pathological mechanism of fructose-induced redox status imbalance and suggest that the enhancement of miR-200a to control Keap1/Nrf2 pathway by polydatin is a therapeutic strategy for fructose-associated liver inflammation and lipid deposition. [Display omitted] •Fructose decreases miR-200a expression to impair Keap1/Nrf2 pathway in NAFLD.•MiR-200a-driven oxidative stress is a causer in fructose-induced NAFLD.•Polydatin elevates miR-200a to regulate Keap1/Nrf2 pathway in fructose-induced NAFLD.•Polydatin lowers fructose-caused oxidative stress, inflammation and lipid deposition.•Enhancement of miR-200a expression by polydatin is a therapeutic strategy for NAFLD.